ATHEROSCLEROSIS IN RELATION TO FAT PENNICULUS (OBESITY) BETWEEN XIPHOID AND UMBILICUS - Naeem, Amjad; Hanif, Ruhila (Journal of Ayub Medical College Abbottabad, 2010)
Background: It has been shown that possible influence of body weight is more evident for coronary than aortic atherosclerosis; and more in men than women. Coronary heart disease due to obesity in males becomes significant when body mass index (BMI) exceeds 30 (30% overweight) and does not affect the life expectancy particularly in women. This study was conducted to asses the relation of thickness of fat penniculus (obesity) between xiphoid and umbilicus to different atherosclerotic lesions; and to collect basic data about age and sex distribution of this relation. Methods: It was prospective descriptive study and conducted at mortuary of King Edward Medical University, and Department of Pathology, Allama Iqbal Medical College, Lahore. A total of 130 human autopsies were carried out in one-and-a-half year of study duration. The ages of the deceased ranged between 8 and 85 years. Heart aorta and its major branches were included in this study. In addition, fat penniculus between xiphoid and umbilicus was measured and atherosclerosis lesions were categorised and correlated with this parameter. Haematoxylin and Eosin, and different special stains were done in Pathology Department of Allama Iqbal Medical College, Lahore to asses to severity of atherosclerosis lesions. Results: The fatty streaks were present in predominantly more cases with Fat Penniculus <20 mm than in asses with Fat Penniculus <10 mm and <30 mm. The fibrolipid plaques, complicated and calcified lesions were present in a dominant number of cases with Fat Penniculus <30 mm on percentage basis. Conclusion: Raised lesions were seen more frequently in cases with Fat Penniculus 20 mm to <30 mm than in cases with Fat Penniculus <10 mm and <20 mm thickness. Keywords: Atherosclerosis, Fat Penniculus, Lesions